Validitas dan Reliabilitas Instrumen CTTMC pada Pembelajaran IPA Terpadu SMP - Marantika Lia Kristyasari (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2021)
The CTTMC instrument is an assessment instrument with a two-tier multiple-choice type, consisting of a first tier and a second tier. Developing an instrument requires data analysis. The data analysis consisted of validity and reliability tests. In the content validity test using the Aiken formula. Content validity analysis data were obtained from 9 validators. The validation process is carried out through a group discussion forum (FGD). The reliability test used Alpha Cronbach's formula with the ITEMAN application. The results of the content validity were more than 0.74, thus indicating that all the developed items were declared valid. While the reliability results obtained were obtained in the medium-scale trial, tier 1 was 0.711 and tier 2 was 0.707, while in the broad-scale trial, tier 1 was 0.833 and tier 2 was 0.873, indicating that the questions developed had high reliability.